Effects of varying degrees of partial bladder outlet obstruction on urinary bladder function of rats: A novel link to inflammation, oxidative stress and hypoxia. Issue 2 (28th December 2017) - Sezginer, Ecem Kaya; Yilmaz‐Oral, Didem; Lokman, Utku; Nebioglu, Serpil; Aktan, Fugen; Gur, Serap
Abstract : Objectives: The aim of the present study was to investigate the effects of different degrees of obstruction, and the roles of inflammation, oxidative stress, and hypoxia parameters on bladder function. Methods: Thirty male Sprague–Dawley rats were divided into 3 groups (n = 10 in each group): (i) sham‐operated control; (ii) severe partial bladder outlet obstruction (PBOO); and (iii) moderate PBOO. Severe and moderate PBOO were induced by urethral ligation using 3‐Fr and 4‐Fr catheters, respectively, for 6 weeks. After 6 weeks, the in vitro contractile responses to carbachol, electrical field stimulation, ATP and KCl were measured in bladder strips. In addition, mRNA and protein expression of nuclear factor kappa B (NF‐κB) hypoxia‐inducible factor (HIF) and nuclear factor, erythroid 2‐like 2 (Nrf2) in bladder were determined by real‐time polymerase chain reaction and western blotting. Malondialdehyde (MDA) levels in bladder tissues were also determined. Results: Rats in the severe PBOO group had the highest bladder weight. Detrusor strips from rats in the severe PBOO group exhibited 61%–82% smaller contractile responses to all four stimuli than those from the sham‐operated group. Activity of NF‐κB as an inflammatory marker was increased in the severe PBOO group, whereas HIF‐1α and HIF‐2β protein levels were increased significantly in the moderate PBOO group. A master regulator of oxidative stress, Nrf2 expression was increased in all obstructed rats. MDA levels were higher in the severe PBOO group than in sham‐operated group. Conclusion: The results of the present study reveal the importance of oxidative stress‐induced NF‐κB signaling in bladder dysfunction with severe obstruction. Altered HIF signaling may contribute to the functional impairment after PBOO. Novel and evolving therapies targeting oxidative and/or inflammatory pathways may be a reasonable strategy for the management of lower urinary tract symptoms or benign prostatic hyperplasia.